Beyond desire : sexuality in modern Tamil literature - Keshavamurthy, Kiran
"This book explores a number of modern Tamil texts featuring men and women who do not always conform to established notions of masculinity and femininity. It also engages with the creative possibilities of a desire that is neither limited to nor exhausted by the sexual act."--Page [4] of cover.